Developing an Efficient Micropropagation Technique for Citrus aurantifolia: Enhancing Mass Production and Germplasm Conservation - Naorem Bela Devi; Soibam Purnima Devi; Punyakishore Maibam (Contemporary Research and Perspectives in Biological Science Vol. 1, 2024)
This study presents an efficient and straightforward method for the micropropagation of Citrus aurantifolia, suitable for mass propagation. The optimal medium for shoot induction was found to be supplemented with 1.5 mg. l-1 of BAP and 1.5 mg. l-1 of KN, yielding a 79.57% response rate and an average of 8.23 shoots per explant. NAA was more effective than IAA for root induction, with a maximum response of 83.52% and an average of 3.24 roots per shoot in medium supplemented with 1.5 mg. l-1 NAA.